Tinjauan Fiqih Muamalah Terhadap Praktik Pengupahan Karyawan Pada Usaha Tempe - Mentari, Melis; Harahap, Zul Anwar Ajim; Hsb, Putra Halomoan (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
The focus of this research is a review of muamalah jurisprudence on employee wage practices in tempe businesses in Penggalangan Village, Sei Bamban District, Serdang Bedagai Regency, by raising two main issues, namely 1) how to implement wage payments between owners and employees in tempe businesses in Penggalangan Village, Sei Bamban District, Regency. Serdang Bedagai? 2) What is Fiqih Muamalah's review of employee wage practices in the tempe business in Penggalangan Village, Sei Bamban District, Serdang Bedagai Regency? The approach used in this research is a qualitative-descriptive approach, namely collecting data by means of interviews, observation and documentation. This research is qualitative, namely research carried out by collecting primary data and secondary data on phenomena that are occurring directly. The primary data from this research is the business owner and three workers in the tempe business in Penggalangan Village, Sei Bamban District, Serdang Bedagai Regency. And the secondary data in this research are books, journals, government publications, and other supporting sites or sources. The results of the research show that the mechanism used in the tempe business in Penggalangan Village, Sei Bamban District, Serdang Bedagai Regency is carried out by means of a verbal agreement, with the contents of the agreement stating that the salary is given in the form of a monthly salary with working hours starting from 07.00-17.00 WIB with a salary of Rp. 750,000 per month. If there is additional work outside the specified time, the business owner will provide an additional salary of Rp. 10,000 per hour. The workers have fulfilled their agreement, but the business owner has not fulfilled what was stated in the verbal agreement, namely not paying wages outside the agreed working hours. Based on the reality of the implementation of the agreement in the tempe business in Penggalangan Village, Sei Bamban District, Serdang Bedagai Regency, in terms of muamalah fiqh, it is contrary to what was agreed (default). It is mentioned in the hadith narrated by Ibnu Maja Rasulullah Saw, who said, which means